A wrinkle in time - L'Engle, Madeleine (New York : Bantam Doubleday Dell Books for Young Readers, 1997)
Meg Murry and her friends become involved with unearthly strangers and a search for Meg's father, who disappeared while engaged in secret work for the government.
5.8.
5.8
5-8
Keywords: Extraterrestrial beings -- Fiction; Friendship -- Fiction; Science fiction; Extraterrestrial beings -- Fiction; Friendship -- Fiction; Science fiction